2002
DOI: 10.1007/s15010-002-2141-y
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Neonatal Outbreak of Serratia marcescens - Analysis of Pathogens by Pulsed Field Gel Electrophoresis and Polymerase Chain Reaction

Abstract: This survey shows that PCR and PFGE are comparable in respect to the discrimination and reproducibility for epidemiological studies of S. marcescens strains in nosocomial outbreaks. Genotypic fingerprinting of bacterial isolates is useful and important to limit nosocomial infections. Fingerprinting sources of nosocomial infections can be traced both by PFGE and PCR. All patients infected recovered completely and the nosocomial outbreak could be stopped rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…9,12,14 Therefore, the rapid typing methods are essential in terms of prompt and sensitive evaluation of S marcescens outbreaks in hospitals and, thus, implementing effective preventive measures when the sources are identified. 15 A number of epidemiological typing methods, including antibiotyping, serotyping, phage typing, plasmid typing, polymerase chain reactionebased typing, and analysis of genomic DNA by PFGE have been described. Antibiograms present little value in most epidemiological studies because isolates with unrelated genetic and epidemiological features have been shown to present the same susceptibility pattern because of the acquisition of the same plasmid by multiple species, named as plasmid outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,14 Therefore, the rapid typing methods are essential in terms of prompt and sensitive evaluation of S marcescens outbreaks in hospitals and, thus, implementing effective preventive measures when the sources are identified. 15 A number of epidemiological typing methods, including antibiotyping, serotyping, phage typing, plasmid typing, polymerase chain reactionebased typing, and analysis of genomic DNA by PFGE have been described. Antibiograms present little value in most epidemiological studies because isolates with unrelated genetic and epidemiological features have been shown to present the same susceptibility pattern because of the acquisition of the same plasmid by multiple species, named as plasmid outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…As in outbreaks that have occurred in adults, genotyping methods have been used in many pediatric outbreaks to type the involved S. marcescens strains, including sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis of disrupted S. marcescens cells (116), plasmid profiling (18,41,157,258), PFGE (52,190,228,239,269,270,309,313,338,341,366,396), ribotyping (150), rep-PCR (239, 393), RAPD-PCR (18), and PCR fingerprinting (366). Voelz and others performed a systematic analysis of several pediatric S. marcescens outbreak studies from 1984 to 2010 that utilized typing procedures to determine clonality.…”
Section: S Marcescensmentioning
confidence: 99%
“…16,17,[40][41][42] Two consecutive clusters (in January-April 2003 and July 2003) by different clones (A and B) and other sporadic cases due to other genotypes were found. The major epidemic-involved pattern A was replaced by different patterns, the cause of which is not clear.…”
Section: And Bothmentioning
confidence: 99%